π - ω interference in the reactions K- p → π+ π- (Λ, ε{lunate}0) at 4.2 GeV/ c - Holmgren, S; Aguilar-Benitez, M; Cerrada, M; Hemingway, R; Losty, M; Worden, R; Jongejans, B; Massaro, G; Wolters, G; Engelen, J; Schotanus, D; Van de Walle, RT; et al. (1977)
π - ω interference is studied in the reactions K- p → π+ π- (Λ0, ε{lunate}) at 4.2 GeV/c using data from a high statistics experiments in the CERN 2m HBC. The phenomenon is analysed in terms of the conventional formalism as well as in terms of a new model for π - ω interference proposed by Earles and Srivastava. Satisfactory agreement with the data is found for both models. The rate of ω → 2π obtained in the latter model is in agreement with the VMD (Vector Meson Dominance) prediction for ω → γ → ρ{variant} → 2π. © 1977.